Dysfunctional monocytic toll-like receptor 4 signaling pathway and cognitive deficits in chronic schizophrenia patients with tardive dyskinesia. (23rd April 2022) - Li, Na; Li, Yanli; Huang, Junchao; Zhang, Ping; Tong, Jinghui; Chen, Song; Cui, Yimin; Tan, Shuping; Wang, Zhiren; Yang, Fude; Hong, Elliot; Li, Chiang-Shan R.; et al.
Highlights: Both TD and NTD patients showed higher TLR4 signal pathway activity at baseline but weaker responses to lipopolysaccharide (LPS), as compared to healthy controls. These trends were less pronounced in TD patients than in NTD patients. In TD patients, TLR4 levels were negatively or positively correlated with MCCB at baseline or after LPS stimulation, respectively. Abstract: Background: Mounting evidence suggests that the innate immune system is disrupted in schizophrenia patients with tardive dyskinesia (TD); however, the role of the toll-like receptor 4 (TLR4) signaling pathway remains unclear. Methods: In this study, we quantified the expression of the monocytic TLR4 signaling pathway using flow cytometry, before and after lipopolysaccharide (LPS) stimulation, in chronic schizophrenia patients with (n = 61) and without TD (NTD, n = 61) and healthy controls (HCs, n = 74). Psychopathological symptoms, the severity of TD, and cognitive function were assessed using the Positive and Negative Syndrome Scale (PANSS), Abnormal Involuntary Movement Scale (AIMS), and MATRICS Consensus Cognitive Battery (MCCB), respectively. Results: 1) Both TD and NTD patients showed higher TLR4 signaling pathway activity at baseline than that in HCs, but their responses to LPS were weaker than those in HCs; 2) the alteration of the TLR4 signaling pathway was less severe in TD patients than in NTD patients; 3) TLR4 levels and MCCB scores were negatively correlated at baseline but positively correlated after LPS stimulation in TD patients; 4) there was no correlation between the TLR4 signals and PANSS or AIMS scores. Conclusions: Our findings suggested the TLR4 signaling pathway disturbance might be related to cognitive deficits in schizophrenia patients with TD.